ANALYSIS COMPETENCE PARTICIPANTS YOUNG AGRICULTURAL ENTREPRENEUR GROWTH PROGRAM (CASE STUDYAT THE POLITEKNIK PEMBANGUNAN PERTANIAN GOWA) - Baja, Wa Ode Nurlintang; Haerani, Siti; Hamid, Nurdjanah (Accounting Profession Journal (APAJI), 2024)
The objective study this, ie to describe the implementation of the PWMP program in Polbangtan Gowa and to analyze the competence PWMP program group. Sample research is the chairman of the PWMP Polbangtan Gowa and the PWMP group that has carried out three PWMP program stages. The method used,ie descriptive qualitative. Research results showthat the implementation of the PWMP program in Polbangtan Gowa has run with Enough GoodBecause stage awareness and growth, as well as stage development businessman, has been carried out.Whereas stage independence entrepreneurial activity includesthe development of network business and assistance not yet applied in a manner maximum. The cause because constrained by the distance between location effort and guidance. The competenceof the PWMP group was assessed as not enough Good in the operating effort. This is because there is a number of effort that is not sustainable and lack work The same for developingthe business so that needed assistance and mentoring periodically.